Acceptability of community health worker and peer supported interventions for ethnic minorities with type 2 diabetes: a qualitative systematic review - Grant, Vivene; Litchfield, Ian (Frontiers in Clinical Diabetes and Healthcare, 2024)
ObjectiveEthnic minority groups in high income countries in North America, Europe, and elsewhere are disproportionately affected by T2DM with a higher risk of mortality and morbidity. The use of community health workers and peer supporters offer a way of ensuring the benefits of self-management support observed in the general population are shared by those in minoritized communities.Materials and methodsThe major databases were searched for existing qualitative evidence of participants’ experiences and perspectives of self-management support for type 2 diabetes delivered by community health workers and peer supporters (CHWPs) in ethnically minoritized populations. The data were analysed using Sekhon’s Theoretical Framework of Acceptability.ResultsThe results are described within five domains of the framework of acceptability collapsed from seven for reasons of clarity and concision: Affective attitude described participants’ satisfaction with CHWPs delivering the intervention including the open, trusting relationships that developed in contrast to those with clinical providers. In considering Burden and Opportunity Costs, participants reflected on the impact of health, transport, and the responsibilities of work and childcare on their attendance, alongside a lack of resources necessary to maintain healthy diets and active lifestyles. In relation to Cultural Sensitivity participants appreciated the greater understanding of the specific cultural needs and challenges exhibited by CHWPs. The evidence related to Intervention Coherence indicated that participants responded positively to the practical and applied content, the range of teaching materials, and interactive practical sessions. Finally, in examining the impact of Effectiveness and Self-efficacy participants described how they changed a range of health-related behaviours, had more confidence in dealing with their condition and interacting with senior clinicians and benefitted from the social support of fellow participants and CHWPs.ConclusionMany of the same barriers around attendance and engagement with usual self-management support interventions delivered to general populations were observed, including lack of time and resource. However, the insight of CHWPs, their culturally-sensitive and specific strategies for self-management and their development of trusting relationships presented considerable advantages.